Sudden unexpected deaths in different age groups at ramathibodi hospital, bangkok, thailand: A Retrospective autopsy study during 2003-2007 - Jitta Udnoon (2018)
A sudden unexpected death is considered one type of medico-legal death in Thailand. In some studies, it comprises up to 50-60% of all medico-legal deaths. In this retrospective study, data were collected from 1,460 cases of sudden unexpected deaths, 39.9% of all deaths in which a medico-legal autopsy had been carried out. The study was conducted over a 5-year period from January 2003 to December 2007. There were 1,009 males and 451 females (M:F ratio = 2.2:1). The mean age was 55.3±0.98 years. The peak age group was the 46-60 years accounting for 28.2% of cases. The most common cause of death in all age groups was coronary atherosclerosis. Understanding epidemiological autopsy data is vital for determining the characteristics of the population involved.